REVIEW : KARAKTERISTIK FISIKOKIMIA DAN STABILITAS PIGMEN ANATTO (Bixa orellana L.) SEBAGAI PEWARNA ALAMI PADA PANGAN - Winda Nurtiana; Dhiya Fathinah; Ghina Aulia; Andrew Christian Handoyo; Zira Rahmadhania; Siti Erisna Wati; Deana Zeni Rofita (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Anatto plant (Bixa orellana L.) is a plant that contains two types of pigments, namely bixin and norboxin. Bixin is the main pigment in kesumba fruit which is non-polar, while norbixin is polar. The utilization of anatto pigment have the potential to serve as a natural coloring agent for food. The physicochemical characteristics of annatto pigments are related to size, shape, boiling point, melting point, solubility, constituent compounds, bonds between atoms, polarity, and chemical reactions. Kesumba seeds can produce annatto pigments through an extraction process. Annatto extraction produces a yellowish orange color obtained from the outer layer of the seeds of the kesumba plant. The method used in the bixin extraction process is the maceration method by soaking the kesumba seeds in a mixture of organic solvents that match the polarity properties of bixin or norbixin pigments. Annatto seed powder has a greater attachment to oil than attachment to water, annatto seed powder has a relatively higher OHC than WHC. The melting point of bixin is 195°C and its boiling point is 280°C while the boiling point of norbixin ranges from 287-289°C and its melting point ranges from 169-170°C. The application of anatto pigment is used in commercial cheese products, cassava crackers, karag crackers, and pork patties. Besides functioning as a colorant, bixin extract can be to supply antioxidants due to its composition containing cartenoids.